2005
DOI: 10.2151/jmsj.83a.291
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Aeolian Dust Observed by Sky-Radiometer in the Intensive Observation Period 1 (IOP1)

Abstract: A sky-radiometer network was developed in order to investigate the characteristics of aeolian dust on the way of transportation from the source region to the Japan area. From the analysis of the skyradiometer data, optical thickness in the visible to near infrared regions and size spectrum from radius 0.01 to 5 mm can be obtained. Five observation sites are set at Aksu, Qira, Shapotou, Qingdao, and Beijing in China, and four observation sites at Naha, Fukuoka, Nagoya and Tsukuba in Japan. The data of six obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…The result is a little bit larger than the retrieved mode radius for the coarse mode (1 to 6 µm) with the skyradiometer observation (Uchiyama et al 2005), but it is reasonable for Kosa particles in the same order of magnitude. The GLI retrieved optical thickness 0.34 at 500nm is larger than the value of 0.30 with a LIDAR measurement at 532 nm (Yasui et al 2005), and, on the other hand, smaller than the value of 0.59 at 500nm with a skyradiometer measurement.…”
Section: Preliminary Results and Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…The result is a little bit larger than the retrieved mode radius for the coarse mode (1 to 6 µm) with the skyradiometer observation (Uchiyama et al 2005), but it is reasonable for Kosa particles in the same order of magnitude. The GLI retrieved optical thickness 0.34 at 500nm is larger than the value of 0.30 with a LIDAR measurement at 532 nm (Yasui et al 2005), and, on the other hand, smaller than the value of 0.59 at 500nm with a skyradiometer measurement.…”
Section: Preliminary Results and Analysismentioning
confidence: 59%
“…where N is a number of particles, r is a particle radius, c is an arbitrary constant which is normalized as a total particle number, r0 is a mode radius, and is a standard deviation, which is expressed as lns The value s is assumed as 2.0 (Uchiyama et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been devoted to measure aerosol optical and physical properties (Holben et al, 2001;Takemura et al, 2002;Dubovik et al, 2002;Smirnov et al, 2002;Nakajima et al, 2003;Aoki and Fujiyoshi, 2003;Kim et al, 2004;Eck et al, 2005). Uchiyama et al (2005) studied the characteristics of aeolian dust observed by sky-radiometer at several sites including some in source region. Li et al (2007) Retrieving from sky-radiometer measured at Anmyeon, Korea, Sohn et al (2007) pointed out that Asian dusts can become more absorbing aerosols when mixed with pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Several international and regional networks of ground-based photometers such as AErosol RObotic NETwork-AERONET (Holben et al 1998), SKYradiometer NETwork-SKYNET (Kim et al 2004;Uchiyama et al 2005), the Global Atmosphere Watch Precision Filter Radiometer-GAW PFR network (Wehrli 2002), and China Aerosol Research Network-CARSNET (Che et al 2009) have been set up over the past 20 years, taking advantage of the development of new instruments and techniques for the systematic observation of optical, microphysical and radiative aerosol properties from the ground.…”
Section: Introductionmentioning
confidence: 99%